Dissemination of the Russian emigrant literature and the literature of the Book Program in East Europe in 1950-1990 - Kazakevičius, Alvydas (Knygotyra, 2024)
Many famous Russian writers, artists, scientists, and public figures lived and worked in emigration. Some of them (M. Dobuzhinskiy, L. Karsavin, J. Mackevich Nord, T. Shuravin, A. Yashchenko, and others) lived and productively worked in independent Lithuania during the pre-war period. Russian emigration and private libraries became a haven where Russian belles-lettres (works of A. Akhmatova, M. Bulgakov, I. Bunin, L. Chukovskaya, etc.) survived.The aim of this research is to expose which organizations, what books in Russian, and by what means were sent to Eastern Europe, especially to Lithuania, between 1950-2000. Until now, the processes of transferring books published abroad to Lithuania and other countries of Eastern Europe have been largely ignored by researchers.There were several Russian émigré political organizations: Russian Socialists, National People's Alliance of Russian Solidarists (NTS), Combatant Union for Russian People's Liberation (SBONR), Combatant Union for Russian Liberty (SBSR), Combatant League for People's Liberty (LBNS), and Central Unification of Political Emigrants from USSR (COPE). They published periodicals, leaflets, pamphlets, books, and strove to disseminate them in the Soviet Union. Alongside the Russian émigré organizations, Russian books abroad were published by the so-called Book Program, Book Exchange Program, religious missions, and some Russian émigré periodicals.In 1950-1956, U.S. governmental institutions adopted the main idea of NTS ideologist and one of its leaders, V. Poremskiy, about the necessity to transfer and disseminate Western books to the people of the Soviet Union. The Chekhov Publishing House was founded in New York. A publishing division of the American-based Free Europe Committee, named "Free Europe Press," was established in New York and Munich. Later, an analogous division of the American Committee for Liberation (Amcomlib), founded in 1951, was formed. "Free Europe Press" started mailing books in 1956. Through this project, thousands of books were posted to Eastern Europe by various addresses. Many Western publishers, periodicals, organizations, and individuals were involved in these activities. A great number of posted books managed to bypass Soviet and Eastern European censors and customs, and some of them reached Lithuania.Some Russian book publishing and dissemination houses were founded to carry out the Book Program: in the late 1950s to early 1960s—COPE Publishers (Munich), Inter-Language Literary Associates (Washington, DC); in 1968-1969—"Overseas Publications Interchange Ltd." (OPI; London), A. Neimanis Buchvertrieb und Verlag (Munich), and others. The publications dissemination network was formed between 1952-1956 and remained active until 1993.The main publishers of Russian religious literature during the 1945-1990 period were "A Life with God" ("La Vie avec Dieu") in Brussels and the Institute for Bible Translation in Stockholm.Some foreign publishers (Ardis Publishers, Chekhov Publishing House) primarily published Russian classics; others ("YMCA-Press," Ardis Publishers, "Possev," Inter-Language Literary Associates, New Chekhov Publishing House) focused on Russian literature of the first half of the 20th century and the newest Russian literature. A third group (COPE Publishers, International Literary Association, "Overseas Publications Interchange Ltd.," A. Neimanis Buchvertrieb und Verlag) published historical, political, publicist works, and memoirs. A fourth group ("Possev," "Overseas Publications Interchange Ltd.," Inter-Language Literary Associates, Alexander Herzen Foundation, "Chronika Press," "Chalidze Publications") published works related to the underground, opposition, and dissenter movements, human rights, and their suppression.Publications of Russian émigrés and other foreign publishers made their way to Lithuania, Russia, and other neighboring countries, and were disseminated through various means: mainly by balloons in the 1950s, by mailings and colporteurs from the late 1950s, by diplomatic mailings, colporteurs, and couriers, by foreign correspondents, and by dissidents from the early 1960s. Lithuanian colporteurs transferred forbidden literature from the USA, West and East Germany, Poland, other countries of Western and Central Europe, as well as from Moscow, Saint Petersburg, Kyiv, and Riga.
Keywords: -